Increasing Aspartoacylase in the Central Amygdala: The Common Mechanism of Gastroprotective Effects of Monoamine-Based Antidepressants Against Stress - Yao, Kaiyun; Cao, Linyu; Ding, Hongwan; Gao, Yinge; Li, Tiegang; Wang, Guibin; Zhang, Jianjun (Frontiers in Pharmacology, 2022)
Monoamine-based antidepressants can prophylactically protect against stress-induced gastric ulcers. Although the central nucleus of amygdala (CeA) has been shown to modulate the severity of stress ulcers, little is known about the molecular mechanisms underlying the gastroprotective effect of this kind of drugs. Here, we first used proton magnetic resonance spectroscopy, a non-invasive tool, to explore the change of neurometabolites of the CeA of rats pretreated with the duloxetine of selective serotonin-norepinephrine reuptake inhibitors during 6 h of water-immersion restraint stress (WIRS). Duloxetine decreased N-acetyl-aspartate/creatine ratio (NAA/creatine) in CeA after WIRS, which was paralleled by the amelioration of gastric lesions. Meanwhile, the gastric ulcer index was negatively correlated with reduced NAA/creatine. Furthermore, the intra-CeA infusion of NAA aggravated WIRS-induced gastric mucosa damage, which suggested the crucial role of reduced NAA. Western blotting was performed to identify the specific enzymes responsible for the change of the contents of NAA at 0.5 h/3 h/6 h after WIRS, considering the preventative gastric protection of duloxetine. The NAA-catabolizing enzyme aspartoacylase (ASPA) was the only enzyme downregulated by 0.5 h WIRS and upregulated by duloxetine. Moreover, overexpressing ASPA in CeA alleviated stress ulcers. Additionally, all of the other three monoamine-based antidepressants, the fluoxetine of selective serotonin reuptake inhibitors, the amitriptyline of tricyclic agents, and the moclobemide of MAOs, increased ASPA expression in CeA. Together, these results indicate that increasing ASPA to hydrolyze NAA in CeA is a common mechanism of gastroprotective effects against stress exerted by monoamine-based antidepressants, and ASPA is a shared target more than monoamine regulation for this kind of drugs.